Which English and Whose Cultures Should Be Taught To Empower Our Students? - Ridwan Arif Nugroho (Universitas Ahmad Dahlan, 2015)
AbstractTomlinson(2010) states that learners of English all over the world are being tested on a variety of English they do not and never will speak. He further emphasizes that the students are being tested on British and American English and not on Singaporean English or Brazilian English or the International English that they speak.Indeed, language and culture are two sides of a coin. The teaching of language cannot be divorced from the teaching of culture. With the emergence of the notion â€œWorld Englishesâ€, it is high time to reconsider which English and whose culture should be taught and introduced to our students. It is the duty of English teachers to determine which English and whose culture to be taught. It is a waste of time, energy, and money to teach a variety of English that has nothing to do with the future life of our students.The paper tries to discuss about the cultural aspects that should be introduced to ourEnglish classes. It is hoped that English teachers realize about the kind of English needed by the students.